Analisis Komunikasi Pemasaran Pada Hotel Salak The Heritage Bogor - Vega Putri Utami; Gati Dwi Yuliana (CoverAge: Journal of Strategic Communication, 2017)
This research is related to marketing communication services. The service product that is the case study of this study is Hotel Salak The Heritage. This study uses the concept of marketing communication and its mix as a blade analysis. The paradigm of this research is postpositivist with qualitative approach. Informants who are the subject of research is representative of Hotel Salak, especially in the field of marketing communications. The research results show Hotel Salak The Heritage tries to combine elements of marketing communication mix by optimizing the potential of ICT (Information and Communication Technology). Elements of marketing communication mix one of them is advertising. The ads are done in various media such as Kompas newspaper, Radio Lesmana FM Bogor, billboards, banners, brochures, websites, social media which includes facebook @, twitter, and instagram. The advertising marketing communication mix is ​​also conducted in conjunction with public relations and sales promotion.